(untitled) (LACCEI, 2024)
The research is aimed at analyzing different models of tourism systems, as well as a comparison between the main theories of supply chains and how they can lead to the design of a new tourism system that integrates more actors in a supply network, in addition, it is presents how much Big Data tools are used in the sector, for this, some interviews and observations were carried out to first identify the actors that are effectively related to the network, as well as the level, use and problems of the actors in the sector. effective use of information to adjust their strategic objectives and sustainability of tourism businesses. It seeks to establish if the information management carried out by the network actors is adequate to improve the service and if they are using Big Data tools that contribute to the improvement of the services that are provided for which they will be used as methods, tools of prospective, AHP and analytical techniques, supported by field visit data, interviews and direct observation Finally, the pertinent recommendations were raised for the improvement of attention to tourists, and to approach green engineering with the improvement of processes hand in hand with conservation and environmental recovery.